Thermodynamic study on hydroxybenzaldehyde derivatives: 3-and 4-Hydroxybenzaldehyde isomers and 3,5-di-tert-butyl-2-hydroxybenzaldehyde - Maria D M C R Ribeiro da Silva (2010)
Reported in the present work are the values of the gaseous standard (p degrees = 0.1 MPa) molar enthalpies of formation of 3-hydroxybenzaldehyde (3HBA), 4-hydroxybenzaldehyde (4HBA), and 3,5-di-tert-butyl-2-hydroxybenzaldehyde (3,5DTBHBA), at T = 298.15 K. For the three compounds, the values were derived from measurements of the standard molar energies of combustion of the crystalline compounds, using a static bomb calorimeter {Delta(c)H degrees m(3HBA) = -(3298.3 +/- 1.3) kJ . mol(-1) . Delta(c)H degrees(m)(4HBA) = -(3291.8 +/- 0.9) kJ . mol(-1) . Delta(c)H degrees(m)(3, 5DTBHBA) = -(8502.6 +/- 2.9) kJ . mol(-1)}, together with the standard molar enthalpies of sublimation, at T = 298.15 K, derived from the vapour pressures measured at different temperatures using the Knudsen effusion technique {Delta(g)(cr)H degrees m(3HBA) = (100.1 +/- 0.6) kJ . mol(-1) . Delta (g)(cr)H degrees(m)(4HBA) = (102.5 +/- 0.5) kJ . mol(-1), Delta(g)(cr)H degrees(m)(3, 5DTBHBA) = (96.0 +/- 0.5) kJ . mol(-1)}